2012
DOI: 10.7309/jmtm.19
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Autonomic Activity Monitoring Among At-Risk Adolescent Mothers

Abstract: Background Many adolescent mothers experience significant challenges in regulating emotions due to adverse life experiences, which can place adolescent mothers and their children at risk for poor developmental outcomes. Ambulatory monitoring of stress that also provides immediate feedback using wearable biosensors has the potential to enhance clinician-delivered parenting interventions and help young mothers develop emotion regulatory skills. Methods We conducted a pilot study to assess the acceptability, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…While Leonard et al [ 28 ] reported qualitative feedback from their participants about their system, they cited a prior pilot conducted with 4 African American or Latinx adolescent mothers from low SES families at high risk for school dropout. Findings indicated participants’ desire to make the sensor bands that measured electrodermal activity (a physiological stress indicator) more comfortable and fashionable in appearance [ 40 ]. Nollen et al [ 29 ] cited previous work that formed a community advisory board (CAB) of adolescent girls, who were primarily racial/ethnic minorities, to provide feedback on the use of the technology platform and to test 2 iterations of prototypes of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…While Leonard et al [ 28 ] reported qualitative feedback from their participants about their system, they cited a prior pilot conducted with 4 African American or Latinx adolescent mothers from low SES families at high risk for school dropout. Findings indicated participants’ desire to make the sensor bands that measured electrodermal activity (a physiological stress indicator) more comfortable and fashionable in appearance [ 40 ]. Nollen et al [ 29 ] cited previous work that formed a community advisory board (CAB) of adolescent girls, who were primarily racial/ethnic minorities, to provide feedback on the use of the technology platform and to test 2 iterations of prototypes of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have demonstrated this in various populations. For example, Page 3735 a study by Rajan S. et al, used a wrist-worn sensor, which measured motion in three axes and EDA, on adolescent mothers to demonstrate the ability to detect stress in a real-world scenario (Rajan et al 2012). In this study, data was streamed directly to the participants' phone and was accessible to them throughout the recorded session.…”
Section: Discussionmentioning
confidence: 99%
“…In our developmental work of the Calm Mom technology [49] and as cited by other reports [57,58], we became keenly aware of the demands mobile health technology can place on participants and the ways in which it can be experienced as irritating or annoying at times. Moreover, we did not want the demands of the Calm Mom technology to distract AMs from their children or tax the cognitive and emotional capacity of these highly overburdened young mothers.…”
Section: Principal Findingsmentioning
confidence: 99%
“…PSP is delivered in-person in a group format by trained interventionists. Calm Mom, is a companion mHealth technology consisting of a smartphone app developed for the study and an integrated wearable sensorband that continually measures EDA [25,49]. The goal of this blended intervention is to increase maternal emotional regulatory skills for more effective parenting and reducing risk behaviors among AMs.…”
Section: Description Of the Blended Intervention Developed For The Prmentioning
confidence: 99%
See 1 more Smart Citation